2018
DOI: 10.1016/j.molp.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses Yield Markers for Identifying Agronomically Important Genes in Potato

Abstract: Wild potato species have substantial phenotypic and physiological diversity. Here, we report a comprehensive assessment of wild and cultivated potato species based on genomic analyses of 201 accessions of Solanum section Petota. We sequenced the genomes of these 201 accessions and identified 6 487 006 high-quality single nucleotide polymorphisms (SNPs) from 167 accessions in clade 4 of Solanum section Petota, including 146 wild and 21 cultivated diploid potato accessions with a broad geographic distribution. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 75 publications
6
58
2
3
Order By: Relevance
“…The authors suggested that, in these crops, germplasm resources are accessible and have received considerable attention from breeders. A recent genomics study revealed a high level of genetic diversity for disease resistance traits in wild potato species [28]. Thus, the case for continued use of germplasm enhancement to improve disease resistance seems strong.…”
Section: Disease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that, in these crops, germplasm resources are accessible and have received considerable attention from breeders. A recent genomics study revealed a high level of genetic diversity for disease resistance traits in wild potato species [28]. Thus, the case for continued use of germplasm enhancement to improve disease resistance seems strong.…”
Section: Disease Resistancementioning
confidence: 99%
“…A large sequencing effort on 84 tomato genomes has recently revealed extensive species-and accession-specific polymorphisms [110]. Similarly, genomic analysis of 201 wild and cultivated potato accessions revealed high levels of diversity, especially in wild populations, and over 600 genes associated with domestication traits [28]. As genome annotation information grows, scientists will be able to identify SNPs in or near genes of interest and predict whether they are likely to result in a functionally different protein product [106].…”
Section: Germplasm Collections In the Genomics Eramentioning
confidence: 99%
“…In potato breeding, hybridization is the main method of creating new populations/forms for selection. The pedigree of modern potato varieties shows that they are obtained by selection from hybrid populations, individual valuable traits, or their combinations, which are absent from the cultural species S. tuberosum (immunity to viruses, late blight, nematode) [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Формирование биосинтетических путей накопления алкалоидов у растений семейства пасленовых происходило в результате дупликаций генов, кодирующих ферменты первичного метаболизма, приводящих к неофункционализации гена, либо вовлечением ферментов первичного метаболизма во вторичный (субфункционализация) и последующей организацией кластеров (Ober, 2005). В последние годы секвенированы геномы дикого картофеля (Li et al, 2018), петунии (Bombarely et al, 2016), перца (Qin et al, 2014), витании (Knoch et al, 2018) с аннотированием генов, реализующих вторичный метаболизм (Aversano et al, 2015;Xu et al, 2017). Геномные данные позволяют проводить филогенетический анализ генов вторичного метаболизма и выявлять события дупликации генов и последующей нео-либо суб-функционализации, либо псевдогенизации и потери функций (D'Amelia et al, 2018;Nagy et al, 2005;Zhang et al, 2015).…”
Section: особенности эволюции геномов семейства пасленовыхunclassified